The new platinum-based anticancer agent LA-12 induces retinol binding protein 4 in vivo - Bouchal, Pavel; Jarkovsky, Jiri; Hrazdilova, Kristyna; Dvorakova, Monika; Struharova, Iva; Hernychova, Lenka; Damborsky, Jiri; Sova, Petr; Vojtesek, Borivoj (Proteome science, 2011)
BACKGROUND: The initial pharmacokinetic study of a new anticancer agent (OC-6-43)-bis(acetato)(1-adamantylamine)amminedichloroplatinum (IV) (LA-12) was complemented by proteomic screening of rat plasma. The objective of the study was to identify new LA-12 target proteins that serve as markers of LA-12 treatment, response and therapy monitoring. METHODS: Proteomic profiles were measured by surface-enhanced laser desorption-ionization time-of-flight mass spectrometry (SELDI-TOF MS) in 72 samples of rat plasma randomized according to LA-12 dose and time from administration. Correlation of 92 peak clusters with platinum concentration was evaluated using Spearman correlation analysis. RESULTS: We identified Retinol-binding protein 4 (RBP4) whose level correlated with LA-12 level in treated rats. Similar results were observed in randomly selected patients involved in Phase I clinical trials. CONCLUSIONS: RBP4 induction is in agreement with known RBP4 regulation by amantadine and cisplatin. Since retinol metabolism is disrupted in many cancers and inversely associates with malignancy, these data identify a potential novel mechanism for the action of LA-12 and other similar anti-cancer drugs.